قواعد المعاملات المالية في تراث ابن دقيق العيد : جمعا ودراسة - حاسي، أحمد علي أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research examined the collection of principles and jurisprudence rulings relating to financial transactions by Imam Ibn Daqiq al-Eid in his rich academic body of work. The research looked at the bifurcation nature of Imam Ibn Daqiq's work since much of the Imam's rulings were overlapping in nature. The research tracked the scattered parts of the topic on financial transaction written by Ibn Daqiq al-Eid in the light of comparative jurisprudence method by comparing it with opinions and evidences on jurisprudence applications. This research concluded that the method of Taq'eed and Ta'aseel was prominently clear in the style of Imam Ibn Daqiq Al-Eid in all of his work through his well-articulated arguments and reasoning. The research also hoped the bifurcation study on imam Ibn Daqiq Al-Eid, Alshatiby and others on the method of Taq'eed and Ta'aseel would increase intellectual discussion in the spirit of the Sharia and the development of Ijtihad and healthy intellectual debate.